Cep55 regulates embryonic growth and development by promoting Akt stability in zebrafish. Issue 5 (9th February 2015) - Jeffery, Jessie; Neyt, Christine; Moore, Wade; Paterson, Scott; Bower, Neil I.; Chenevix‐Trench, Georgia; Verkade, Heather; Hogan, Benjamin M.; Khanna, Kum Kum
ABSTRACT: CEP55 was initially described as a centrosome‐ and midbody‐associated protein and a key mediator of cytokinesis. More recently, it has been implicated in PI3K/AKT pathway activation via an interaction with the catalytic subunit of PI3K. However, its role in embryonic development is unknown. Here we describe a cep55 nonsense mutant zebrafish with which we can study the in vivo physiologic role of Cep55. Homozygous mutants underwent extensive apoptosis by 24 hours postfertilization (hpf) concomitant with cell cycle defects, and heterozygous carriers were indistinguishable from their wild‐type siblings. A similar phenotype was also observed in zebrafish injected with a cep55 morpholino, suggesting the mutant is a cep55 loss‐of‐function model. Further analysis revealed that Akt was destabilized in the homozygous mutants, which partially phenocopied Akt1 and Akt2 knockdown. Expression of either constitutively activated PIK3CA or AKT1 could partially rescue the homozygous mutants. Consistent with a role for Cep55 in regulation of Akt stability, treatment with proteasome inhibitor, MG132, partially rescued the homozygous mutants. Taken together, these results provide the first description of Cep55 in development and underline the importance of Cep55 in the regulation of Pi3k/Akt pathway and in particular Akt stability.—Jeffery, J., Neyt, C., Moore, W., Paterson, S., Bower, N. I., Chenevix‐Trench, G., Verkade, H., Hogan, B. M., Khanna, K. K. Cep55 regulates embryonic growth and development by promoting Akt stability in zebrafish. FASEB J. 29, 1999‐2009 (2015). www.fasebj.org